2018
DOI: 10.1242/jcs.213595
|View full text |Cite
|
Sign up to set email alerts
|

Novel role for Grainy head in the regulation of cytoskeletal and junctional dynamics during epithelial repair

Abstract: Tissue repair is critical for the maintenance of epithelial integrity and permeability. Simple epithelial repair relies on a combination of collective cell movements and the action of a contractile actomyosin cable at the wound edge that together promote the fast and efficient closure of tissue discontinuities. The Grainy head family of transcription factors (Grh in flies; GRHL1-GRHL3 in mammals) are essential proteins that have been implicated both in the development and repair of epithelia. However, the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 94 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…Transcription factors belonging to the highly conserved Grainyhead family act as important regulators of epidermal morphogenesis, wound healing, and barrier function [10][11][12][13][14][15][16]. Consistent with this, the three mammalian Grainyhead-like (Grhl) paralogs control the expression of genes important for cell adhesion and extracellular barrier repair.…”
Section: Introductionmentioning
confidence: 76%
“…Transcription factors belonging to the highly conserved Grainyhead family act as important regulators of epidermal morphogenesis, wound healing, and barrier function [10][11][12][13][14][15][16]. Consistent with this, the three mammalian Grainyhead-like (Grhl) paralogs control the expression of genes important for cell adhesion and extracellular barrier repair.…”
Section: Introductionmentioning
confidence: 76%
“…[29] As a member of the GRHL family, GRHL1 plays an important role in regulating embryogenesis, embryonic development, formation of the epidermal barrier and repair of epidermal injury. [30][31][32][33] Furthermore, a great number of research have shown that the GRHL1 acted as a tumor suppressive factor in carcinogenesis, progression and prognosis of various cancer types including liver cancer, skin cancer, neuroblastoma and clear cell renal cell carcinoma. [34] GRHL1 plays a critical role in fate determination of pluripotent cells, which might be relevant to phenotypic plasticity in tumors.…”
Section: Discussionmentioning
confidence: 99%